What Do Test Scores in Texas Tell Us? - Klein et al, Stephen P.; Hamilton, Laura; McCaffrey, Daniel F.; Stecher, Brian (Education Policy Analysis Archives, 2000)
We examine the results on the Texas Assessment of Academic Skills (TAAS), the highest-profile state testing program and one that has recorded extraordinary recent gains in math and reading scores. To investigate whether the dramatic math and reading gains on the TAAS represent actual academic progress, we have compared these gains to score changes in Texas on another test, the National Assessment of Educational Progress (NAEP). Texas students did improve significantly more on a fourth-grade NAEP math test than their counterparts nationally. But, the size of this gain was smaller than their gains on TAAS and was not present on the eighth-grade math test. The stark differences between the stories told by NAEP and TAAS are especially striking when it comes to the gap in average scores between whites and students of color. According to the NAEP results, that gap in Texas is not only very large but increasing slightly. According to TAAS scores, the gap is much smaller and decreasing greatly. Many schools are devoting a great deal of class time to highly specific TAAS preparation. While this preparation may improve TAAS scores, it may not help students develop necessary reading and math skills. Schools with relatively large percentages of minority and poor students may be doing this more than other schools. We raise serious questions about the validity of those gains, and caution against the danger of making decisions to sanction or reward students, teachers and schools on the basis of test scores that may be inflated or misleading. Finally, we suggest some steps that states can take to increase the likelihood that their test results merit public confidence and provide a sound basis for educational policy.